The power of maps - Bringing the third dimension to the negotiation table - Pedrick, Clare (Technical Centre for Agricultural and Rural Cooperation, 2016)
Participatory geographic information systems (PGIS) combine a range of geo-spatial information management tools and methods such as sketch maps, participatory 3D models (P3DM), aerial photographs, satellite images, global positioning systems (GPS) and geographic information systems (GIS). CTA has been in the forefront of activities to promote PGIS across African, Caribbean and Pacific countries. Impact assessments undertaken in all six ACP regions have documented how empowering PGIS can be for rural and at times marginalised communities. This publication documents some of the success stories that have emerged as a result of CTA’s initiatives in PGIS in recent years. We are firmly committed to building the capacities of our partners to make better use of PGIS, so they can have a voice in the development of sound policies for agricultural development and sustainable management of natural resources.